2000
DOI: 10.1055/s-0038-1634261
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Recovery from Depressive Illness by an Exponential Model with Mixed Effects

Abstract: Abstract:In clinical trials of antidepressant treatments, a depression rating score is usually measured at several points of time for each patient. We propose an approach to fit data from this type of clinical trial using an exponential mixed-effects model. Compared to previous proposals, this approach has the advantage that individual recovery curves are fitted rather than curves of means. Furthermore, no artificial fixing of model parameters is needed as in other approaches. The flexibility of the proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Recent work by Priest et al [23] and by Friede et al [9] has shown that the time course of the HAMD total score during recovery from depression can be described by fitting an exponential regression model to the data. While such models can describe the data actually observed during a trial, they may also be used to predict the future recovery process beyond the end of the period of observation.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Priest et al [23] and by Friede et al [9] has shown that the time course of the HAMD total score during recovery from depression can be described by fitting an exponential regression model to the data. While such models can describe the data actually observed during a trial, they may also be used to predict the future recovery process beyond the end of the period of observation.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…While such models can describe the data actually observed during a trial, they may also be used to predict the future recovery process beyond the end of the period of observation. For our trial, exponential recovery curves were determined, which showed a good model fit to the observed treatment group means (for details, see [9]). The Hypericum groups recovery curve was substantially steeper, indicating a faster HAMD total score decrease.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…However, probably most important of all from a clinical point of view, the figure also shows that in both dimensions the difference between Hypericum extract and placebo increased over time: while the response curves of the patients treated with placebo tended to flat out between treatment days 14 and 42, this was not the case in the Hypericum group. Priest and colleagues (1996; see also Friede et al 2000) have demonstrated with reference to the time course of the HAMD total score that recovery from depression can be described by fitting an exponential model. By extrapolating the time courses in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmacological antidepressant treatments have been shown to exhibit a nonlinear pattern of treatment response, with relatively large improvements in symptoms in the first weeks followed by smaller but continued improvements approaching a plateau 19 21 . This decrease in depressive symptoms has been modeled using an exponential decay function across multiple medications 22 24 . The exponential decay model suggests a defined relationship between early clinical response and eventual treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%